HGG-11. LEPTOMENINGEAL DISEASE AND TUMOR DISSEMINATION ALONG CSF PATHWAYS IN A MURINE DIPG MODEL: IMPLICATIONS FOR STUDY OF THE TUMOR-CSF-EPENDYMAL MICROENVIRONMENT. (1st June 2021) - Pan, Shelei; Ye, Dezhuang; Yue, Yimei; Yang, Lihua; Pacia, Christopher; Dahiya, Sonika; Limbrick, David; Rubin, Joshua; Chen, Hong; Strahle, Jennifer
Abstract: Background: Leptomeningeal disease and hydrocephalus are present in up to 30% of patients with diffuse intrinsic pontine glioma (DIPG), however there are no animal models of cerebrospinal fluid (CSF) dissemination. As the tumor-CSF-ependymal microenvironment may play an important role in tumor pathogenesis, we identified characteristics of the Nestin-tumor virus A (Nestin-Tva) genetically engineered mouse model (GEMM) that make it ideal to study the interaction of tumor cells with the CSF and its associated pathways with implications for the development of treatment approaches to address CSF dissemination in DIPG. Methods: A Nestin-TVa model of DIPG utilizing the three most common DIPG genetic alterations (H3.3K27M, PDGF-B, p53) was used for this study. All animals underwent MR imaging and a subset underwent histopathologic analysis with H&E and beta-IV tubulin. Results: Tumor dissemination within the CSF pathways (ventricles, leptomeninges) was present in 76% (25/33) of animals, with invasion of the choroid plexus, disruption of the ciliated ependyma and regional subependymal fluid accumulation. Ventricular enlargement consistent with hydrocephalus was present in 94% (31/33). Ventricle volume correlated with region specific transependymal CSF flow (periventricular T2 signal), localized anterior to the lateral ventricles. Subependymal tumor cells were also present subjacent to the 4th ventricle in a post-mortem human specimen. Conclusions: This is the first study to report CSF pathway tumor dissemination an animal model of DIPG and is representative of CSF dissemination seen clinically. Understanding the CSF-tumor-ependymal microenvironment has significant implications for treatment of DIPG through targeting mechanisms of tumor spread within the CSF pathways.